A glimpse into the world of the hearing-impaired RVN. Issue 7 (3rd July 2017) - Campbell, Emma Joanne
Abstract: Being hearing-impaired in everyday life can be a challenge in itself; however, when I started at my current job I found the staff were fascinated by my implant. To me, my implant is a normal part of my life and quite often I forget that other people may have questions about how I hear compared to them. I thought I would try and answer a few of these questions on behalf of some of the other hearing-impaired Veterinary Nurses I have communicated with. Hopefully it will give some insight into how some VNs deal with being in practice.